2008
DOI: 10.1002/elan.200704215
|View full text |Cite
|
Sign up to set email alerts
|

Employment of Electrochemical Techniques for Metallothionein Determination in Tumor Cell Lines and Patients with a Tumor Disease

Abstract: In the present paper we employed adsorptive transfer stripping technique coupled with chronopotentiometric stripping analysis for determination of metallothionein (MT) in tumor cell lines and differential pulse voltammetry Brdicka reaction for determination of MT in blood serum of patients with head and neck cancer or retinoblastoma, and of rats treated with cisplatin with respect to discuss the role of MT in formation of resistance on treatment with heavy metal based cytostatics. The cisplatin or carboplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 60 publications
1
35
0
3
Order By: Relevance
“…Moreover, this marker has been found elevated even in other types of cancers such as breast carcinoma [66], head and neck cancer [67], medulloblastoma [35], melanoma [68,69] and other [70][71][72][73][74]. Nevertheless, combination of MT and PSA levels could be of prognostic significance due to possible revealing of false positive results, but this assumption needs to be investigated in greater details.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this marker has been found elevated even in other types of cancers such as breast carcinoma [66], head and neck cancer [67], medulloblastoma [35], melanoma [68,69] and other [70][71][72][73][74]. Nevertheless, combination of MT and PSA levels could be of prognostic significance due to possible revealing of false positive results, but this assumption needs to be investigated in greater details.…”
Section: Resultsmentioning
confidence: 99%
“…MT content in the cell lines was quantified by dot intensities using Biolight software. Typical DIA results and dependence of MT content on applied Cd Electrochemical methods are often used for MT determination in different types of biological samples like animal tissues, blood, blood serum, and cell lines with low relative standard deviation [58,86]. These methods are based on detection of hydrogen evolution from the supporting electrolyte catalyzed by the presence of -SH and -NH 2 groups of a protein or peptide.…”
Section: Influence Of CD 21 On Mt Level In Human Fibroblastsmentioning
confidence: 99%
“…It has been recently demonstrated that metallothioneins play an important role in the development and progression of some tumour diseases (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Enhanced levels of MT in tumour cells are probably closely connected with cell proliferation (43,44).…”
Section: Introductionmentioning
confidence: 99%